PENINGKATAN KEMAMPUAN BERBICARA MELALUI STRATEGI PEMBELAJARAN DRAMATISASI PADA MATA PELAJARAN BAHASA INDONESIA - Sumani Sumani (LPPM UNISDA, 2018)
The objectives to be achieved in this study are: (1) Overcoming the difficulties of speaking properly and correctly, and (2) improving student learning outcomes through a Dramatization strategy on Indonesian Language subjects in fifth grade students of Lebakadi II Elementary School, Sugio Subdistrict, Lamongan District, 2017 Academic Year / 2018. This research takes place in 2 cycles, each cycle consists of 4 stages: planning, implementing actions, observing, and reflecting. Data collected in the form of observational data on teacher activity, student active role, and competency test scores. The results showed that there was an increase in teacher activity which had not been optimal (before the cycle) increased to 75% (cycle I), and in the second cycle the teacher's activity was 100%. Student activity and achievement which was originally low 55.28 (before the cycle) rose to 62.96% (cycle I). In the second cycle, several variations of treatment were carried out to increase student activity and achievement to increase to 75.93%. It can be concluded that: (1) The use of dramatization strategies in Indonesian language learning can overcome the good and right speaking difficulties, and (2) the learning outcomes of students at Lebakadi II Elementary School in Sugio District in learning Indonesian through the Dramatization strategy can increase.